2020
DOI: 10.4251/wjgo.v12.i12.1416
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological characteristics and prognosis of 77 cases with type 3 gastric neuroendocrine tumours

Abstract: BACKGROUND For the rarity of type 3 gastric neuroendocrine tumours (g-NETs), their clinicopathological characteristics and prognosis are not well illustrated. AIM To describe the clinicopathological features and outcome of type 3 g-NETs in the Chinese population. METHODS Based on the 2019 WHO pathological classification, the clinicopathological characteristics and prognosis of patients with type 3 g-NETs in China were retrospectively analysed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 38 publications
2
10
0
Order By: Relevance
“…Only one in 121 patients developed a metastasis during follow-up. Type 3 g-NENs may therefore be candidates for endoscopic resection if they are < 20 mm, show only submucosal invasion, and have a negative gallium-68 dotatoc scan beforehand [92][93][94].…”
Section: Guidelinementioning
confidence: 99%
“…Only one in 121 patients developed a metastasis during follow-up. Type 3 g-NENs may therefore be candidates for endoscopic resection if they are < 20 mm, show only submucosal invasion, and have a negative gallium-68 dotatoc scan beforehand [92][93][94].…”
Section: Guidelinementioning
confidence: 99%
“…In 21 studies, the origin of the tumor site was predominantly the gastric corpus/fundus (83.3%) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ], and prevalent polypoid morphology from endoscopy was identified in 13 out of the 31 studies [ 15 , 16 , 17 , 20 , 21 , 22 , 23 , 25 , 26 , 28 , 29 , 30 , 31 ]. A total of 17 out of the 31 studies included tumor depth invasion data, resulting in an invasion that included the submucosa in most cases [ 15 , 16 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 28 , 30 , 32 , 34 , 35 , 36 , 37 , 38 ]. A total of 26 out of the 31 papers reported dimensional data, and the median size was 16.5 mm (8–62.5 mm) [ 14 ,…”
Section: Resultsmentioning
confidence: 99%
“…A total of 26 out of the 31 papers reported dimensional data, and the median size was 16.5 mm (8–62.5 mm) [ 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 23 , 24 , 26 , 28 , 31 , 32 , 34 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ]. Six out of thirty-one authors reported a cut-off size of >10 mm for low tumor-related death [ 16 , 17 , 18 , 19 , 21 , 39 ], while 7 out of the 31 papers reported a larger cut-off size of >20 mm for an increased risk of gastric wall infiltration, metastasis at diagnosis, and relapse ( p < 0.001) [ 14 , 22 , 23 , 24 , 26 , 43 , 44 ]. A total of 3 out of the 31 authors showed a higher risk of gastric wall infiltration (and then lymph node and distant metastasis at diagnosis) with a cut-off of >17 and >19 mm [ 30 , 37 , 38 ], while two authors shared a stricter cut-off of <5 mm for sharing an indication of endoscopic management [ 37 , 39 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Type III gNENs have always been considered to be invasive tumors. In a retrospective analysis of 77 patients with type III gNENs, Li et al [ 5 ] found lymph node metastases and distant metastases in ten (13.0%) patients with G2 gNENs, and 24 (31.2%) patients with G3 gNENs. In this study, two patients with type III gNENs were found to have liver metastases, including one case of G2 and one case of G3.…”
mentioning
confidence: 99%